New data for the Early Upper Paleolithic of Kostenki (Russia). Issue 127 (February 2019) - Dinnis, Rob; Bessudnov, Alexander; Reynolds, Natasha; Devièse, Thibaut; Pate, Abi; Sablin, Mikhail; Sinitsyn, Andrei; Higham, Thomas
Abstract: Several questions remain regarding the timing and nature of the Neanderthal-anatomically modern human (AMH) transition in Europe. The situation in Eastern Europe is generally less clear due to the relatively few sites and a dearth of reliable radiocarbon dates. Claims have been made for both notably early AMH and notably late Neanderthal presence, as well as for early AMH (Aurignacian) dispersal into the region from Central/Western Europe. The Kostenki-Borshchevo complex (European Russia) of Early Upper Paleolithic (EUP) sites offers high-quality data to address these questions. Here we revise the chronology and cultural status of the key sites of Kostenki 17 and Kostenki 14. The Kostenki 17/II lithic assemblage shares important features with Proto-Aurignacian material, strengthening an association with AMHs. New radiocarbon dates for Kostenki 17/II of ∼41–40 ka cal BP agree with new dates for the recently excavated Kostenki 14/IVw, which shows some similarities to Kostenki 17/II. Dates of ≥41 ka cal BP from other Kostenki sites cannot be linked to diagnostic archaeological material, and therefore cannot be argued to date AMH occupation. Kostenki 14's Layer in Volcanic Ash assemblage, on the other hand, compares to Early Aurignacian material. New radiocarbon dates targeting diagnostic lithics date to 39–37 ka cal BP. Overall, Kostenki's early EUP is in good agreement with the archaeological record further west. Our results are therefore consistent with models predicting interregional penecontemporaneity of diagnostic EUP assemblages. Most importantly, our work highlights ongoing challenges for reliably radiocarbon dating the period. Dates for Kostenki 14 agreed with the samples' chronostratigraphic positions, but standard pre-treatment methods consistently produced incorrect ages for Kostenki 17/II. Extraction of hydroxyproline from bone collagen using preparative high-performance liquid chromatography, however, yielded results consistent with the samples' chronostratigraphic position and with the layer's archaeological contents. This suggests that for some sites compound-specific techniques are required to build reliable radiocarbon chronologies.